Exchanging layout and schedule data in a real-time distributed environment - Zouein, P. (2017)
Unpredictable site conditions and unforeseen changes in construction work may result in inefficiencies due to a shortage of work space and difficult access to critical areas on site. This hampers productivity. Detailed advance planning of site space use over time and reorganization of the work may alleviate these inefficiencies. An interactive decision support tool is presented that loosely integrates layout with resource scheduling to make it easier to plan operations for which timing and space use are critical. Layouts for consecutive time frames, which together span the duration of construction, are created one at a time by the user. When a layout is identified as problematic because of spatial conflict, the user calls upon the scheduler to remedy the problem by delaying activities, changing resource allocation levels or resource types. The modified schedule is returned to the user who then proceeds with the layout task. The architecture and operation of this tool are described. A first version has been implemented. It brings to bear key issues in space-time cost trade-off and provides a test bed for experimentation with real-time distributed computing for site materials management. Tools like the one presented here allow for better advance planning that leads to improved field productivity.